New Challenges for the Pressure Evolution of the Glass Temperature - Rzoska, Sylwester J. (Frontiers in Materials, 2017)
The ways of portrayal of the pressure evolution of the glass temperature (Tg) beyond the dominated Simon-Glatzel-like pattern are discussed. This includes the possible common description of Tg(P) dependences in systems described by dTg/dP>0 and dTg/dP<0. The latter is associated with the maximum of Tg(P) curve hidden in the negative pressures domain. The issue of volume and density changes along the vitrification curve is also noted. Finally, the universal pattern of vitrification associated with the crossover from the low density (isotropic stretching) to the high density (isotropic compression) systems is proposed. Hypothetically, it may obey any glass former, from molecular liquids to colloids.